2022
DOI: 10.1186/s13018-022-03103-7
|View full text |Cite
|
Sign up to set email alerts
|

Disappointment and frustration, but long-term satisfaction: patient experiences undergoing treatment for a chronic Achilles tendon rupture—a qualitative study

Abstract: Background Delayed treatment of Achilles tendon ruptures is generally due to either misdiagnosis or patient delay. When the treatment is delayed more than 4 weeks, the rupture is defined as “chronic”, and almost always requires more invasive surgery and longer rehabilitation time compared with acute Achilles tendon ruptures. There is insufficient knowledge of patient experiences of sustaining and recovering from a chronic Achilles tendon rupture. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Previous research has indicated that delayed treatment of Achilles tendon injuries can affect outcomes, with early intervention often leading to better prognosis. 20,21 The fact that a significant portion of our participants underwent surgery between 6 to 10 weeks post-injury suggests a potential delay in seeking or receiving treatment, which could be a factor in the final outcomes observed. The cause of injury in our study, predominantly due to sharp-metal objects (57.14%) and toilet-pan incidents (35.71%), is somewhat atypical compared to the commonly reported sports-related causes in other literatures.…”
Section: Discussionmentioning
confidence: 97%
“…Previous research has indicated that delayed treatment of Achilles tendon injuries can affect outcomes, with early intervention often leading to better prognosis. 20,21 The fact that a significant portion of our participants underwent surgery between 6 to 10 weeks post-injury suggests a potential delay in seeking or receiving treatment, which could be a factor in the final outcomes observed. The cause of injury in our study, predominantly due to sharp-metal objects (57.14%) and toilet-pan incidents (35.71%), is somewhat atypical compared to the commonly reported sports-related causes in other literatures.…”
Section: Discussionmentioning
confidence: 97%
“…The most common cause is the misdiagnosis of acute Achilles tendon rupture. A missed diagnosis rate of approximately 20% has been reported in several studies [26, 29, 40]. Chronic rupture of the Achilles tendon often leads to severe calf muscle dysfunction and gait abnormalities and surgical intervention is generally required [6, 16, 27, 30, 39].…”
Section: Introductionmentioning
confidence: 99%